“Because he was disgusting”: transforming relations through positioning in messenger-supported group psychotherapy - Kabatnik, Susanne (Frontiers in Psychology, 2024)
Introduction This article deals with positioning in messenger-supported group psychotherapy in terms of transforming relations. The aim of the messenger-supported therapy format is to work through conflicts that have arisen with people via messenger services. This is achieved in different phases of conversation, such as describing the situation, analysing one's own behaviour and defining wishes, by collaboratively drafting a message to the person from the conflict. Methods The data basis is a corpus of 14 video-recorded group psychotherapy sessions. Methodologically, the study is guided by interactional linguistics, a linguistic research field that focuses on interpersonal interaction. Results Using a case study, I show how the interactants work through a conflict through positioning, constitute group identity and relationships, and thus also transform their stance concerning the issue. Moreover, positioning serves the collaborative formulation of a message and thus also the change of the relationship to the person from the messenger communication. Discussion Relationship management in eSA group psychotherapy can be observed on different levels: (1) among the interactants in the room, (2) with the persons from the chat messages, and (3) between the patient(s) and the therapist.